High susceptibility to liver injury in IL‐27 p28 conditional knockout mice involves intrinsic interferon‐γ dysregulation of CD4+ T cells1. Issue 4 (12th February 2013) - Zhang, Song; Liang, Ruifang; Luo, Wei; Liu, Chang; Wu, Xiaoli; Gao, Yanan; Hao, Jianlei; Cao, Guangchao; Chen, Xi; Wei, Jun; Xia, Siyuan; Li, Zheng; et al.
Abstract Interleukin (IL)‐27, a newly discovered IL‐12 family cytokine, is composed of p28 and EBI3. In this study, CD11c‐p28f/f conditional knockout mice were generated to delete p28 specifically in dendritic cells (DCs). We demonstrated that in the absence of DC‐derived p28, these mice were highly susceptible to both low and higher concentrations of concanavalin A (ConA) (5 mg/kg or 10 mg/kg), with extremely early and steady high levels of interferon‐γ (IFN‐γ) in sera. Neutralizing IFN‐γ prevented ConA‐induced liver damage in these mice, indicating a critical role of IFN‐γ in this pathological process. Interestingly, the main source of the increased IFN‐γ in CD11c‐p28f/f mice was CD4+ T cells, but not natural killer T (NKT) cells. Depletion of CD4+, but not NK1.1+, cells completely abolished liver damage, whereas transferring CD4+ T cells from CD11c‐p28f/f mice, but not from wild‐type mice or CD11c‐p28f/f‐IFN‐γ−/− double knockout mice to CD4−/− mice, restored the increased liver damage. Further studies defined higher levels of IFN‐γ and T‐bet messenger RNA in naïve CD4+ T cells from CD11c‐p28f/f mice, and these CD4+ T cells were highly responsive to both low and higher concentrations of anti‐CD3, indicating a programmed functional alternation of CD4+ T cells. Conclusion: We provide a unique model for studying the pathology of CD4+ T cell–mediated liver injury and reveal a novel function of DC‐derived p28 on ConA‐induced fulminant hepatitis through regulation of the intrinsic ability for IFN‐γ production by CD4+ T cells. (HEPATOLOGY 2013)